A New Approach to Determine the Flexural Stiffness Coefficient for Reinforced Concrete Shear Walls According to Non-Linear Behaviour - Foroughi, Saeid; Yuksel, S. Bahadir (International Journal of Integrated Engineering, 2025)
The precision in calculating the stiffness of reinforced concrete sections is critical for establishing accurate values for structural stiffness and the associated seismic loads. This study investigated effective stiffnesses recommended for use in designing and analysing structures. A total of 135 section models with transverse and longitudinal reinforcement ratios, compressive strength of concrete and axial load levels affecting the analytical analysis of the nonlinear behavior of reinforced concrete shear walls with high ductility levels were considered. The key parameters influencing effective stiffness an aspect that encompasses the impact of cracking and theoretical yielding within structural sections were identified through thorough moment-curvature analyses conducted on a range of shear wall sections. According to the numerical analysis results of the shear wall models, it was found that these design parameters were effective on the stiffness coefficient of the sections. Considering the effective stiffness of section models, a secure and simpler equation is proposed to include these parameters. The equation provides a high degree of accuracy in design and analysis by considering the nonlinear behavior of shear walls in buildings concerning important design parameters. Based on the results of the nonlinear analysis, the proposed predictions for the effective stiffness coefficient, relations proposed by many researchers, standards, and codes, are verified by comparisons with moment-curvature relations. The proposed equation for the effective stiffness of shear wall sections with high ductility levels offers fairly accurate and consistent estimates since it considers all design parameters that affect the non-linear behavior of the sections. This equation has been compared with nonlinear analyses of section models and existing relationships in the literature and has been proven to be reasonably accurate for practical engineering design applications. In the proposed equation, the stiffness coefficients of shear walls can be calculated according to these effective design parameters, and it can verify and design high ductility shear walls with sufficient accuracy in practical engineering design and analysis applications.